Numerical modeling of non-equilibrium heat and mass transfer processes in a reactor for the production of porous titanium - Tsaplin, Aleksey Ivanovich; Nechaev, Vladimir Nikolaevich (Computational Continuum Mechanics, 2013)
A mathematical model is proposed to describe the dynamics of non-equilibrium heat and mass transfer in the process of magnesium-thermal recovery of titanium from its tetrachloride. For the axially symmetric computational domain in the two-layer system with a permeable interface between the molten magnesium and the porous titanium, the boundary value problem is formulated in terms of temperature-vortex-stream function variables. An algorithm for performing computational experiments is described. With allowance made for conjugate processes at the interface between the molten magnesium and the titanium, the results of numerical simulation of the temperature field, stream function and pressure are presented.
Keywords: porous titanium; molten magnesium; heat and mass transfer; mathematical model